Mingkatkan Kemampuan Guru Produktif Membuat Rencana Pelaksanan Pembelajaran (RPP) Melalui Supervisi Klinis Di SMK Negeri 1 Bebandem Tahun 2019/ 2020 - I Wayan Darmayasa (Cetta: Jurnal Ilmu Pendidikan, 2021)
The reality in the field is that it is found that many teachers have not made a Learning Implementation Plan (RPP) in accordance with the Permendikbud, this is because, among others: (1) The teacher does not completely understand how to compile the RRP, as a result of the lack of information they get, (2) the teacher not able to describe the syllabus into the main lesson plans in preparing learning activities, (3) Meanwhile, many teachers use ready-made lesson plans that are not suitable for school situations and conditions, (4) There is an assumption from the teacher that the lesson plan (RPP) is a complement mere administration. This is evident from the results of preliminary observations with teachers regarding the preparation of lesson plans, it turns out that the results are quite low, namely Productive Teachers in the TBSM Expertise Competency score 54, in the TAV Skills Competency the score is 48, in the AP Expertise Competency the score is 59 and in the TB Skills Competency the score is 61. Objectives This study is to determine whether clinical supervision can improve the ability of productive teachers at SMKN 1 Bebandem to make Learning Implementation Plans. The method used to collect data follows the steps used in clinical supervision, namely: interview, observation, question and answer, discussion and document study. The data analysis method used to analyze the data is descriptive analysis, both qualitative and quantitative. Based on the results of research that has been carried out for two cycles of productive teachers at SMK Negeri 1 Bebandem, it shows that there is an increase in the ability to compile a Learning Implementation Plan (RPP) through a clinical supervision approach. Based on the assessments obtained in cycle I and cycle II using the clinical supervision approach, the implementation of the actions taken can be said to be able to improve the ability of productive teachers at SMK Negeri 1 Bebandem in compiling a Learning Implementation Plan (RPP). The conclusion from this study is that the clinical supervision approach can improve the ability of productive teachers at SMK Negeri 1 Bebandem in compiling a Learning Implementation Plan (RPP). This is evident from the increase in the ability of Productive teachers in the TBSM Skills Competency from an initial value of 54 to increase to 84 in cycle I and to 96 in cycle II. Productive teachers in the TAV Skills Competency from the initial acquisition of 48 increased to 75 in cycle I and increased to 93 in cycle II. Whereas Productive teachers in the AP Skills Competency from the initial acquisition of 59 rose to 81 in cycle I and rose to 95 in cycle II, and for Productive teachers in the Catering Skills Competency from the initial acquisition of 61 in cycle I and up to 95 in cycle II.